People's Republic of China-Hong Kong Special Administrative Region : 2011 Article IV Consultation Discussions. (IMF Staff Country Reports; Country Report, 2011)
The Executive Board of the IMF has concluded the consultation discussions with the Hong Kong Special Administrative Region (SAR). Hong Kong SAR has rebounded from the global financial crisis, and growth should be at 5 3/4 percent this year. Unemployment has fallen to low levels, and real incomes have grown, supporting consumption. It is noted that growth has rebounded thanks to the authorities' policy response, highly flexible labor and product markets, and favorable spillovers from Mainland China. The progress on increasing trade settlement and issuing financial instruments denominated in renminbi has accelerated.